Predicting formation of adhesions after gynaecological surgery: development of a risk score - Lundorff, Per; Brölmann, Hans; Koninckx, Philippe Robert; Mara, Michal; Wattiez, Arnaud; Wallwiener, Markus; Trew, Geoffrey; Crowe, Alison M.; De Wilde, Rudy Leon (Archives of gynecology and obstetrics, 2015)
Risk factors for post-surgical adhesions following gynaecological surgery have been identified, but their relative importance has not been precisely determined. No practical tool exists to help gynaecological surgeons evaluate the risk of adhesions in their patients. The purpose of the study was to develop an Adhesion Risk Score to provide a simple tool that will enable gynaecological surgeons to routinely quantify the risk of post-surgical adhesions in individual patients.